Knowledge Level of Saffron Growers in Ghorian District of Heart in Afghanistan - Faiz, Abdullah; Sultani, Mahbob Shah; Fazely, Abdul Sattar (International Journal of Bio-resource and Stress Management, 2015)
Saffron (Crocus sativus L.) is the most precious and expensive spice in the world. It is one of the important commercial crops in Afghanistan. Several historical testimonies, dated around 2,000 years ago, mention that saffron was cultivated in Afghanistan. Since the saffron re-cultivation and introduction started by 2002, the farmer’s knowledge on package of practices remain conspicuous. The present study was conducted in Ghorian district of Herat province in Afghanistan during September 2012 to assess the knowledge level of the saffron growers regarding recommended cultivation practices. A total of 120 saffron farmers from Posht-e-Hesar and Bazarcha were interviewed using a pre-tested schedule. The over-all knowledge level of farmers varied significantly. About 66% of saffron growers had medium, 21.5% high and 12.5% low level of knowledge of recommended practices. Among the 120 farmers interviewed, 95.8-98.3% had correct knowledge on duration of the recommended corm, corm rate, fungi control, suitable month for sowing, number of stigma in each flower, appropriate weight for corm, recommended corm, earthing-up , crust-breaking after planting and annually. Age, education, land holding and mass media participation of saffron growers had a positive and significant relationship with knowledge level. Hence, a series of educational activities should be undertaken by the agencies which focus on the good agricultural practices to improve the knowledge level of farmers.